Chelovek i zakon . Chelovek i zakon . People and the Law . Человек и закон - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The position of Russian servicemen in Germany; segment on a teenager who inadvertently killed his classmate playing with a hunting gun; interview with a Krishna worshipper about the end of the world. Contributors: Krauze, IUrii (Anchor) Положение российских военнослужащих в Германии; сюжет о подростке, нечаянно убившем своего школьного товарища в результате игры с охотничьим ружьем; интервью с кришнаитом о конце света. Создатели: Краузе, Юрий (Ведущий/Ведущая)